A processing method of low-precipitation corrosion-resistant stainless steel and low-precipitation corrosion-resistant stainless steel
Patent Information
- Application Number
- CN202611254417.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]传统电子烟结构件多采用304或316L奥氏体不锈钢,这些材料在常规烟油中表现出较好的耐蚀性,但在6-甲基尼古丁烟油长期接触下,普通不锈钢会发生点蚀、晶间腐蚀,并导致镍、铬、铁等重金属离子的微量析出
[0015]与现有技术相比,本发明的有益效果是:本发明通过冶炼、热处理、表面处理等步骤的组合,使不锈钢材料获得极其致密光滑的表面钝化膜,抑制了离子析出。通过优化合金成分,显著降低在弱酸性烟油中的重金属析出,并提高抗点蚀和抗晶间腐蚀能力。具体表现在:
Smart Images

Figure CN122879588A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic cigarette atomization material manufacturing technology, specifically to a processing method for low-precipitation corrosion-resistant stainless steel. It also relates to a low-precipitation corrosion-resistant stainless steel prepared using the aforementioned processing method. Background Technology
[0002] With the development of e-cigarette technology, novel nicotine salt systems (such as 6-methylnicotine derivatives) are widely used due to their high stability and high delivery efficiency. 6-methylnicotine is a new generation of synthetic nicotine derivatives. Compared with traditional natural nicotine, the 6-methylnicotine molecule contains multiple methyl polar groups in its side chain. 6-methylnicotine e-liquid has a highly polar organic amine structure and a strong ability to complex metal ions.
[0003] Traditional electronic cigarette components mostly use 304 or 316L austenitic stainless steel. These materials exhibit good corrosion resistance in regular e-liquids, but under long-term contact with 6-methylnicotine e-liquid, ordinary stainless steel will experience pitting corrosion and intergranular corrosion, leading to the trace precipitation of heavy metal ions such as nickel, chromium, and iron. This metal ion precipitation not only accelerates the oxidation and discoloration of e-liquid and produces an unpleasant taste, but also poses potential health risks. Currently, using high-nickel alloys or pure titanium can improve corrosion resistance, but these are costly and difficult to process; using organic coatings carries the risk of peeling off. Therefore, there is an urgent need to develop a stainless steel material and its processing technology that exhibits extremely low precipitation of 6-methylnicotine e-liquid, excellent corrosion resistance, moderate cost, and ease of forming. Summary of the Invention
[0004] To address the problems in the prior art, this invention provides a processing method for low-precipitation corrosion-resistant stainless steel.
[0005] The present invention provides a method for processing low-precipitation corrosion-resistant stainless steel, comprising the following steps: S1: Weigh a certain amount of stainless steel raw materials and mix them, then smelt and cast the raw materials to obtain stainless steel ingots. S2: Heat the ingot to a certain holding temperature and perform homogenization annealing. The holding time is 30 h + (10~15 min / mm)×a, where a is the thickness of the ingot. Then, hot roll it to obtain a stainless steel plate with a certain shape. S3: Heat to the second set temperature range and hold for a set time to perform a solution treatment on the stainless steel sheet, and then quickly cool to room temperature; S4: The stainless steel sheet is processed into the shape of the target part by cold rolling or stamping to obtain the target part; S5: Electropolishing the target part removes micro-protrusions and stress damage layers formed during machining from the surface of the target part, resulting in a smooth, clean and glossy surface. S6: Perform surface treatment on the target part after electropolishing to form a dense and smooth passivation film on the surface of the target part; S7: Clean and dry the surface-treated target parts to obtain the final stainless steel product.
[0006] Furthermore, in step S1, a dual process of vacuum induction melting and electroslag remelting is used for smelting and ingot casting.
[0007] Furthermore, in step S2, the heat preservation temperature is 1180 ℃~1250 ℃, and the hot rolling forming adopts a gradient temperature, rolling multiple times in the range of 1050-1180℃, so that the stainless steel sheet forms a uniform fine grain structure.
[0008] Further, in step S4, the cold rolling is at least one of unidirectional rolling 16%, bidirectional rolling 16%, unidirectional rolling 20%, and bidirectional rolling 20%.
[0009] Further, in step S5, the target part is placed in a phosphoric acid-sulfuric acid electrolyte with a current density of 15~25A / dm², a temperature of 55℃~70℃, and a time of 3~8 minutes, so that the surface roughness Ra ≤ 0.05μm.
[0010] Furthermore, in step S6, the surface treatment includes nanosecond laser irradiation, passivation with a compound alkaline solution, or acid passivation.
[0011] Furthermore, the nanosecond laser irradiation process is as follows: irradiation is performed using a laser with a wavelength of 1064 nm, a pulse frequency range of 20 kHz to 50 kHz, a maximum pulse width of 240 ns, and a power adjustment range of 0 to 200 W. During the laser irradiation process, the distance between the target part and the lens is always maintained at the lens focal length measurement value.
[0012] Furthermore, the passivation method of the compound alkaline solution is as follows: the target part is immersed in an alkaline solution of NaNO2, NaOH, and Na3PO4·12H2O, and passivated at a second set temperature for a second set time.
[0013] The present invention also provides a low-precipitation corrosion-resistant stainless steel, which is prepared by the processing method of the aforementioned low-precipitation corrosion-resistant stainless steel.
[0014] Furthermore, the low-emission corrosion-resistant stainless steel is suitable for 6-methylnicotine e-liquid environments, and the low-emission corrosion-resistant stainless steel comprises the following components by mass percentage: nickel (Ni) 8%~16%; chromium (Cr) 13%~18%; molybdenum (Mo) 1%~2%; manganese (Mn) 1%~2%; copper (Cu) 0.5%~3%; silicon (Si) 1%~3%; carbon (C) 0.04%~0.08%; nitrogen (N) 0.04%~0.14%; sulfur (S) 0.005%~0.03%; phosphorus (P) 0.03%~0.045%; with the remainder being iron (Fe).
[0015] Compared with existing technologies, the beneficial effects of this invention are: This invention, through a combination of smelting, heat treatment, and surface treatment steps, enables stainless steel materials to obtain an extremely dense and smooth surface passivation film, inhibiting ion precipitation. By optimizing the alloy composition, it significantly reduces the precipitation of heavy metals in weakly acidic soda oil and improves resistance to pitting corrosion and intergranular corrosion. Specifically, this is manifested in: 1. The high chromium, high molybdenum, and high nitrogen composition of the stainless steel material of the present invention endows the material with super strong resistance to general corrosion, pitting corrosion and crevice corrosion. Even after long-term use, when the passivation film is partially damaged, the high corrosion resistance of the substrate itself can effectively delay the occurrence and development of corrosion. 2. This invention possesses excellent surface quality and long-term stability. After processing through smelting, heat treatment, and surface treatment, the surface of the target part is as smooth as a mirror, making it difficult for tar-like substances from e-liquid to adhere to the wall or absorb, and easy to clean. The stable microstructure and high-quality passivation film ensure that the performance of the component remains stable after thousands of heating-cooling cycles, and will not affect the normal use of the electronic cigarette due to material aging or corrosion. 3. This invention possesses excellent processing performance and wide applicability. The stainless steel prepared by this invention belongs to the category of austenitic stainless steel, maintaining good plasticity and toughness, and is easily formed using conventional cold and hot working methods. Therefore, this invention is not only suitable for e-cigarette oil storage tanks, but can also be widely applied to all metal parts that come into contact with e-liquid, such as atomizer core bases, airway tubes, and metal mouthpieces. Attached Figure Description
[0016] To more clearly illustrate the solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0017] Figure 1 This is a flowchart of the processing method for low-precipitation corrosion-resistant stainless steel according to the present invention. Detailed Implementation
[0018] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention; the terms "comprising" and "having," and any variations thereof, in the specification, claims, and foregoing drawings are intended to cover non-exclusive inclusion. The terms "first," "second," etc., in the specification, claims, or foregoing drawings are used to distinguish different objects, not to describe a particular order.
[0019] In this invention, the reference to "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment to other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described in this invention can be combined with other embodiments.
[0020] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0021] like Figure 1 As shown, the present invention provides a method for processing low-emission corrosion-resistant stainless steel suitable for 6-methylnicotine e-liquid environments, comprising the following steps: S1: Weigh a certain amount of stainless steel raw materials and mix them. Then, smelt and cast the raw materials to obtain stainless steel ingots.
[0022] In this step, a dual process of vacuum induction melting and electroslag remelting is used for smelting and casting to obtain ingots with low gas content and high purity.
[0023] S2: The ingot is heated to a certain holding temperature and then homogenized and annealed for a holding time of 30 h + (10~15 min / mm)×a, where a is the thickness of the ingot in mm. Then it is hot rolled to obtain a stainless steel plate with a certain shape.
[0024] In this step, the heat preservation temperature in this example is 1180 ℃~1250 ℃, and the basic heat preservation time is 30h. As the thickness of the ingot increases, the heat preservation time also increases gradually, so that the present invention can achieve homogenized annealing, which is used to remove defects such as shrinkage cavities and porosity formed during solidification and to adjust the internal microstructure, and then hot rolling is performed.
[0025] Preferably, the hot rolling forming in this example adopts a gradient temperature, and multiple rolling passes are performed in the range of 1050-1180℃, so that the stainless steel sheet forms a uniform fine-grained structure.
[0026] In this example, during the hot rolling process, the initial rolling was carried out in a relatively high temperature range (1150–1180 °C) to reduce the material deformation resistance and improve the plasticity and formability of the ingot. Subsequently, as the number of rolling passes increased, the temperature gradually decreased to 1100–1150 °C to promote dynamic recovery and dynamic recrystallization within the material and improve the deformed structure. In the subsequent temperature range of 1050–1100 °C, multiple rolling passes were carried out to further refine the grains and achieve a homogenized structure, ultimately obtaining a hot-rolled billet with a uniform fine-grained structure.
[0027] S3: Heat to the second set temperature range and hold for the set time to perform a solution treatment on the stainless steel sheet, then quickly cool to room temperature.
[0028] In this step, the second set temperature is 1080 ℃~1150 ℃, and the holding time for solution treatment is 60~300 min. In this example, rapid water quenching to room temperature is used. Of course, other cooling methods such as air cooling can also be used. The purpose of this step is to suppress the precipitation of carbides, obtain a completely solidified austenitic single-phase structure, and ensure the good mechanical properties and excellent corrosion resistance of stainless steel.
[0029] S4: The stainless steel sheet is processed into the shape of the target part by cold rolling or stamping to obtain the target part.
[0030] In this step, if cold rolling is selected, unidirectional rolling of 16%, bidirectional rolling of 16%, unidirectional rolling of 20%, or bidirectional rolling of 20% can be used. Since the stainless steel material after solution treatment in this invention belongs to the category of austenitic stainless steel, it maintains good plasticity and toughness and is easy to process and form.
[0031] S5: Electropolishing the target part removes microscopic protrusions and stress damage layers formed during machining, resulting in a smooth, clean, and glossy surface.
[0032] In this step, the target part is placed in a phosphoric acid-sulfuric acid electrolyte at a current density of 15-25 A / dm², a temperature of 55℃-70℃, and a time of 3-8 minutes, until the surface roughness Ra ≤ 0.05 μm. This example utilizes the principle of anodic dissolution to preferentially remove microscopic protrusions and stress-damaged layers formed during machining from the material surface, resulting in an extremely smooth (nanoscale roughness), clean, and glossy surface. This smooth surface reduces the area for corrosive media adhesion and the initiation points for localized corrosion.
[0033] S6: Perform surface treatment on the target part after electropolishing to form a dense and smooth passivation film on the surface of the target part. In this step, the surface treatment includes nanosecond laser irradiation, compound alkaline solution passivation, or acid passivation, etc. Through surface treatment, the defect layer and surface active area generated by machining can be removed, and the passivation film can be strengthened to reduce the probability of medium corrosion.
[0034] S7: Clean and dry the surface-treated target parts to obtain the final stainless steel product.
[0035] In this step, the target part can be immersed in acetone and alcohol and ultrasonically cleaned for 10-15 minutes, then dried with cold air. In this example, the volume ratio of acetone to alcohol is 1:1.
[0036] As can be seen from the above, the present invention, through a combination of smelting, heat treatment, and surface treatment steps, enables stainless steel materials to obtain an extremely dense and smooth surface passivation film, effectively suppressing ion precipitation.
[0037] This invention features excellent surface quality and long-term stability. After processing through smelting, heat treatment, and surface treatment, the surface of the target part is as smooth as a mirror, making it less prone to adhering to or absorbing tar-like substances from e-liquid, and easy to clean. The stable microstructure and high-quality passivation film ensure that the component's performance remains stable after thousands of heating-cooling cycles, and that the normal use of the e-cigarette is not affected by material aging or corrosion.
[0038] In step S6, the nanosecond laser irradiation process is as follows: Irradiation is performed using a laser with a wavelength of 1064 nm, a pulse frequency range of 20 kHz to 50 kHz, a maximum pulse width of 240 ns, and a power adjustment range of 0 to 200 W. During the laser irradiation process, the distance between the target part and the lens is always maintained at the lens focal length measurement value to ensure precise laser beam focusing, avoid defocusing or near-focusing, and ensure that the sample receives uniform and stable laser irradiation. In this example, a YLPN-10-30x240-200-R laser (IPG 200W laser) can be used, with a lens focal length measurement value of 15.73 cm.
[0039] The passivation method using the compound alkaline solution is as follows: the target part is immersed in an alkaline solution composed of NaNO2, NaOH, and Na3PO4·12H2O, and passivated at a second set temperature for a second set time. The NaNO2 mass concentration is 15 g / L, the NaOH mass concentration is 10 g / L, and the Na3PO4·12H2O mass concentration is 25 g / L, with passivation at 105 ℃ for 1 h.
[0040] The acid passivation method involves immersing the target part in a 20% (w / w) acid solution and adding 0.5 wt% EDTA as a complexing agent, then passivating at 50 °C for a certain time. Preferably, the acid solution used in the acid passivation method is at least one of nitric acid and citric acid, and the passivation time is 30 min, 1 h, 3 h, etc.
[0041] The present invention also provides a low-precipitation corrosion-resistant stainless steel, which is prepared by the processing method of the aforementioned low-precipitation corrosion-resistant stainless steel.
[0042] Preferably, the low-emission corrosion-resistant stainless steel is suitable for 6-methylnicotine e-liquid environments, and the low-emission corrosion-resistant stainless steel comprises the following components by mass percentage: nickel (Ni) 8%~16%; chromium (Cr) 13%~18%; molybdenum (Mo) 1%~2%; manganese (Mn) 1%~2%; copper (Cu) 0.5%~3%; silicon (Si) 1%~3%; carbon (C) 0.04%~0.08%; nitrogen (N) 0.04%~0.14%; sulfur (S) 0.005%~0.03%; phosphorus (P) 0.03%~0.045%; with the remainder being iron (Fe).
[0043] This invention significantly reduces the precipitation of heavy metals in weakly acidic e-liquids and improves resistance to pitting and intergranular corrosion by optimizing the alloy composition. Specifically, the high chromium, high molybdenum, and high nitrogen composition of the stainless steel material of this invention endows the material with superior resistance to general corrosion, pitting corrosion, and crevice corrosion. Even after long-term use, when the passivation film shows localized damage, the high corrosion resistance of the substrate itself can effectively delay the occurrence and development of corrosion.
[0044] This invention possesses excellent processing performance and wide applicability. The stainless steel prepared by this invention belongs to the category of austenitic stainless steel, maintaining good plasticity and toughness, and is easily formed using conventional cold and hot working methods. Therefore, this invention is not only suitable for e-cigarette oil storage tanks, but can also be widely applied to all metal parts that come into contact with e-liquid, such as atomizer core bases, airway tubes, and metal mouthpieces.
[0045] The present invention will be further described in detail below with reference to specific embodiments. Unless otherwise specified, the reagents and raw materials used in the following embodiments are all metallurgical grade high-purity raw materials with a purity of ≥99.9%; all process equipment and testing equipment are industry-standard metallurgical equipment; and all chemical components are expressed as mass percentages.
[0046] Example 1: Example 1 provides a low-emission, corrosion-resistant stainless steel suitable for 6-methylnicotine e-liquid environments. Its chemical composition, by mass percentage, is as follows: Nickel Ni 16% Chromium (Cr) 18% Molybdenum 2% Copper Cu 3% Silicon (Si) 1% Carbon (C) 0.04% Nitrogen (N) 0.1% Sulfur (S) 0.03% Phosphorus (P) 0.045% Manganese (Mn) 2% The remaining content is all iron (Fe).
[0047] The processing method of the low-precipitation corrosion-resistant stainless steel of the present invention is as follows: S1: Smelting and casting: Weigh a certain amount of raw materials according to the above mass percentage, mix them evenly, and then use a dual process of vacuum induction melting and electroslag remelting to obtain a casting with low gas content and high purity. S2: Heat the ingot to 1200 ℃ for homogenization annealing. The holding time is determined according to the actual thickness of the ingot and the extended time is used to remove defects such as shrinkage cavities and porosity formed during solidification and to adjust the internal structure. Then, multi-pass rolling is carried out in the range of 1050-1180℃ using a three-stage gradually decreasing temperature gradient to form a uniform fine-grained structure. S3: Solution treatment: The stainless steel sheet is solution treated by heating to 1100 ℃ and holding for 100 min, followed by rapid water quenching to room temperature. The purpose is to suppress the precipitation of carbides, obtain a fully solution-treated austenitic single-phase structure, and ensure the good mechanical properties and excellent corrosion resistance of the stainless steel. S4: Cold working and forming: The sheet metal is processed into the target part shape by unidirectional rolling of 16%; S5: Electrolytic Polishing: The target part is placed in a phosphoric acid-sulfuric acid electrolyte at a current density of 15~25 A / dm², a temperature of 60℃, and a time of 5 minutes, until the surface roughness Ra ≤ 0.05 μm. This removes microscopic protrusions and stress damage layers formed during machining from the material surface, resulting in an extremely smooth (nanoscale roughness), clean, and glossy surface. The smooth surface reduces the area for corrosive media adhesion and the initiation points for localized corrosion. S6: Surface treatment: The target part substrate after electropolishing is subjected to acid passivation treatment. In this example, the sample is immersed in a 20% citric acid solution and 0.5 wt% EDTA is added as a complexing agent, and passivation is performed at 50 °C for 3 h. S7: Cleaning and Drying: After surface treatment, immerse the target part in acetone and alcohol and clean it with ultrasonic cleaning for 12 minutes, then dry it with cold air.
[0048] Examples 2-8 provide a low-emission corrosion-resistant stainless steel suitable for 6-methylnicotine e-liquid environments, the chemical composition of which is shown in Table 1 by mass percentage, with the remainder being iron and unavoidable impurities.
[0049] Table 1 Content of each component in Examples 2-8 NickelNi 8% 13% 16% 16% 16% 16% 16% 16% Chromium (Cr) 18% 18% 18% 18% 18% 18% 18% 18% Molybdenum 2% 2% 2% 2% 2% 2% 2% 2% Copper Cu 3% 3% 3% 3% 3% 3% 3% 3% Silicon (Si) 1% 1% 3% 2% 1% 1% 1% 1% Carbon C 0.04% 0.04% 0.04% 0.04% 0.08% 0.06% 0.04% 0.04% Nitrogen N 0.1% 0.1% 0.1% 0.1% 0.1% 0.1% 0.14% 0.04% Sulfur S 0.03% 0.03% 0.03% 0.03% 0.03% 0.03% 0.03% 0.03% Phosphorus P 0.045% 0.045% 0.045% 0.045% 0.045% 0.045% 0.045% 0.045% Manganese (Mn) 2% 2% 2% 2% 2% 2% 2% 2% Example 10: Example 9 provides a low-emission corrosion-resistant stainless steel suitable for 6-methylnicotine e-liquid environments. Its formulation, dosage, and preparation method are the same as those in Example 1. The difference is that the surface treatment time of the S6 acid passivation method in the processing technology of the prepared stainless steel is 30 min.
[0050] Example 11: Example 10 provides a low-precipitation corrosion-resistant stainless steel suitable for 6-methylnicotine e-liquid environments. Its formulation, dosage, and preparation method are the same as those in Example 1. The difference is that the surface treatment time of the S6 acid passivation method in the processing technology of the prepared stainless steel is 1 hour.
[0051] Example 12: Example 11 provides a low-precipitation corrosion-resistant stainless steel suitable for 6-methylnicotine e-liquid environments. Its formulation, dosage, and preparation method are the same as those in Example 1. The difference is that the acid used in the S6 acid passivation surface treatment process of the prepared stainless steel is nitric acid.
[0052] Example 13: Example 12 provides a low-precipitation corrosion-resistant stainless steel suitable for 6-methylnicotine e-liquid environments. Its formulation, dosage, and preparation method are the same as those in Example 1. The difference is that the S6 surface treatment process in the processing technology of the prepared stainless steel is a compound alkaline solution passivation method.
[0053] Example 14: Example 13 provides a low-emission corrosion-resistant stainless steel suitable for 6-methylnicotine e-liquid environments. Its formulation, dosage, and preparation method are the same as those in Example 1. The difference is that the S6 surface treatment process in the processing technology of the prepared stainless steel is nanosecond laser irradiation.
[0054] Comparative Example 1: Comparative Example 1 provides a low-emission corrosion-resistant stainless steel suitable for 6-methylnicotine e-liquid environments. Its formulation, dosage, and preparation method are the same as those in Example 1. The difference is that the S6 surface treatment process is not performed in the processing of the prepared stainless steel.
[0055] Experimental Results: The target parts obtained in the above embodiments and Comparative Example 1 were immersed in a simulated e-liquid solution containing 2.5 mg / mL 6-methylnicotine in propylene glycol-glycerol mixture for 30 days at a constant temperature of 60 ℃. The amount of major metal ions precipitated in the e-liquid was determined by inductively coupled plasma mass spectrometry, and the corrosion morphology of the sample surface was observed by scanning electron microscopy. The test results are shown in Table 2.
[0056] Table 2. Metal ion deposition and surface condition of each target component in a 6-methylnicotine e-liquid environment. Example 1 1.8 0.35 0.18 0.12 +1.12 No pitting, glossy Example 2 4.3 0.95 0.62 0.35 +0.98 Very slight pitting Example 3 3.5 0.72 0.55 0.28 +1.01 No pitting Example 4 2.5 0.48 0.29 0.17 +1.03 No pitting Example 5 2.3 0.4 0.25 0.15 +1.08 No pitting Example 6 5.2 0.66 0.85 0.38 +0.82 Minor pitting Example 7 4.9 0.58 0.66 0.29 +1.00 No pitting Example 8 2.1 0.39 0.3 0.23 +1.01 No pitting Example 9 3.5 0.61 0.49 0.39 +0.86 Minor pitting Example 10 3.8 0.78 0.5 0.24 +0.81 Minor pitting Example 11 3 0.6 0.36 0.22 +0.95 Minor pitting Example 12 3.6 0.72 0.45 0.27 +0.83 Minor pitting Example 13 2.7 0.58 0.33 0.21 +1.01 No pitting Example 14 2.5 0.5 0.3 0.18 +1.05 No pitting Comparative Example 1 12.6 3.5 1.8 1.2 +0.62 Obvious pitting A comparison of Examples 1 and 2-3 reveals that increasing the Ni content improves the pitting corrosion resistance of stainless steel.
[0057] A comparison of Examples 1 and 4-5 reveals that Si can improve the corrosion resistance of heat-resistant steel in strong oxidizing media, but excessive Si content can increase the material's brittleness. Similar to the effect of Cr, Si reacts with oxygen at high temperatures to form spinel-structured oxides, which are tightly bonded to the matrix. Therefore, adding an appropriate amount of Si to heat-resistant steel can not only improve its heat resistance but also enhance its resistance to high-temperature oxidation.
[0058] A comparison of Examples 1 and 6-7 reveals that a higher carbon content results in a looser iron oxide scale structure and better peelability. Due to the strong affinity between carbon and chromium, carbon readily forms chromium carbide precipitates, which not only induces intergranular corrosion but also leads to chromium depletion in grain boundary regions, thus inhibiting the formation of the protective oxide film and weakening its adhesion to the metal substrate. Furthermore, under high-temperature oxidation conditions, carbon, due to its low solubility and slow diffusion rate in the oxide film, tends to accumulate at the oxide layer-substrate interface and reacts with oxygen to generate volatile gases such as CO and CO2. When gas escape is obstructed, localized internal pressure can form, causing the oxide film to rupture. As the oxidation temperature increases, the oxide film thickness gradually increases, and its structural integrity decreases accordingly, exacerbating the damage.
[0059] Examples 1, 8, and 9 show that solid solution of nitrogen can improve the pitting corrosion resistance of materials and enhance corrosion resistance by forming nitrides. However, excessive nitrogen content may lead to excessive precipitation of nitrides, thus adversely affecting the overall performance of the material. Therefore, in practical applications, it is necessary to rationally control the nitrogen content in the steel according to the specific service environment to achieve the optimal balance between structural stability and corrosion resistance.
[0060] A comparison of Examples 1 and 10-12 revealed that citric acid passivation for 3 h was superior to that for 1 h and 30 min, and the citric acid system was significantly better than nitric acid in inhibiting copper precipitation.
[0061] A comparison of Examples 1 and 13-14 reveals that the passivation method using nanosecond laser irradiation and a compound alkaline solution resulted in slightly lower metal precipitation control and passivation film stability compared to Example 1. Nanosecond laser irradiation reduces corrosion-active sites by improving the surface microstructure, but due to the absence of a complexation cleaning process, the metal ion precipitation control effect is slightly lower than in Example 1. The passivation film formed by the compound alkaline solution passivation method exhibits slightly lower stability and acid resistance compared to the citric acid system.
[0062] Based on the combined findings of Example 1 and Comparative Example 1, Comparative Example 1, due to the absence of S6 surface treatment, did not effectively remove the defect layer and surface active area generated by machining, and the surface also failed to form a dense and smooth passivation film, making it easier for corrosive media to penetrate, ultimately exhibiting the highest metal precipitation and the lowest pitting potential.
[0063] As can be seen from the above, through the synergistic effect of optimized alloy composition and multi-step processing technology, the components prepared by this invention show a significant reduction in the amount of key heavy metal ions such as nickel and chromium released during tests simulating the harsh working conditions of electronic cigarettes. The stainless steel products exhibit excellent corrosion resistance, superior surface quality, and long-term stability in the environment of 6-methylnicotine e-liquid.
[0064] The specific embodiments described above are preferred embodiments of the present invention and are not intended to limit the specific scope of the present invention. The scope of the present invention includes, but is not limited to, these specific embodiments. All equivalent changes made in accordance with the present invention are within the protection scope of the present invention.
Claims
1. A processing method for low-precipitation corrosion-resistant stainless steel, characterized in that, Includes the following steps: S1: Weigh a certain amount of stainless steel raw materials and mix them, then smelt and cast the raw materials to obtain stainless steel ingots. S2: Heat the ingot to a certain holding temperature and perform homogenization annealing. The holding time is 30 h + (10~15 min / mm)×a, where a is the thickness of the ingot. Then, hot roll it to obtain a stainless steel plate with a certain shape. S3: Heat to the second set temperature range and hold for a set time to perform a solution treatment on the stainless steel sheet, and then quickly cool to room temperature; S4: The stainless steel sheet is processed into the shape of the target part by cold rolling or stamping to obtain the target part; S5: Electropolishing the target part removes micro-protrusions and stress damage layers formed during machining from the surface of the target part, resulting in a smooth, clean and glossy surface. S6: Perform surface treatment on the target part after electropolishing to form a dense and smooth passivation film on the surface of the target part; S7: Clean and dry the surface-treated target parts to obtain the final stainless steel product.
2. The processing method for low-precipitation corrosion-resistant stainless steel according to claim 1, characterized in that: In step S1, a dual process of vacuum induction melting and electroslag remelting is used for smelting and ingot casting.
3. The processing method for low-precipitation corrosion-resistant stainless steel according to claim 1, characterized in that: In step S2, the heat preservation temperature is 1180 ℃~1250 ℃, and the hot rolling forming adopts a gradient temperature, rolling multiple times in the range of 1050-1180℃, so that the stainless steel sheet forms a uniform fine grain structure.
4. The processing method for low-precipitation corrosion-resistant stainless steel according to claim 1, characterized in that: In step S4, the cold rolling is at least one of unidirectional rolling 16%, bidirectional rolling 16%, unidirectional rolling 20%, and bidirectional rolling 20%.
5. The processing method for low-precipitation corrosion-resistant stainless steel according to claim 1, characterized in that: In step S5, the target part is placed in a phosphoric acid-sulfuric acid electrolyte with a current density of 15~25A / dm², a temperature of 55℃~70℃, and a time of 3~8 minutes, so that the surface roughness Ra ≤ 0.05μm.
6. The processing method for low-precipitation corrosion-resistant stainless steel according to claim 1, characterized in that: In step S6, the surface treatment includes nanosecond laser irradiation, passivation with a compound alkaline solution, or acid passivation.
7. The processing method for low-precipitation corrosion-resistant stainless steel according to claim 6, characterized in that: The nanosecond laser irradiation process is as follows: irradiation is performed using a laser with a wavelength of 1064 nm, a pulse frequency range of 20 kHz to 50 kHz, a maximum pulse width of 240 ns, and a power adjustment range of 0 to 200 W. During the laser irradiation process, the distance between the target part and the lens is always maintained at the lens focal length measurement value.
8. The processing method for low-precipitation corrosion-resistant stainless steel according to claim 6, characterized in that: The passivation method using the compound alkaline solution is as follows: the target part is immersed in an alkaline solution composed of NaNO2, NaOH, and Na3PO4·12H2O, and passivated at a second set temperature for a second set time.
9. A low-precipitation corrosion-resistant stainless steel, characterized in that: It is prepared by the processing method of the low precipitation corrosion-resistant stainless steel according to any one of claims 1-8.
10. The low-precipitation corrosion-resistant stainless steel according to claim 9, characterized in that: The low-emission corrosion-resistant stainless steel is suitable for 6-methylnicotine e-liquid environments, and comprises the following components by weight percentage: Nickel Ni 8%~16%; Chromium (Cr) 13%~18%; Molybdenum 1%~2%; Manganese (Mn) 1%~2%; Copper (Cu) 0.5%~3%; Silicon (Si) 1%~3%; Carbon (C) content: 0.04%~0.08%; Nitrogen (N) 0.04%~0.14%; Sulfur (S) 0.005%~0.03%; Phosphorus (P) 0.03%~0.045%; The remaining content is iron (Fe).